Application of Ce for scavenging Cu impurities in A356 Al alloys. Issue 1 (13th January 2022) - Sims, Zachary C.; Henderson, Hunter B.; Thompson, Michael J.; Chaudhary, Rakesh P.; Hammons, Joshua A.; Ilavsky, Jan; Weiss, David; Anderson, Kevin; Ott, Ryan; Rios, Orlando
Abstract: Secondary (recycled) Al is increasingly used in castings due to its lower cost and carbon footprint relative to primary Al. However, the presence of certain impurity elements in secondary Al degrades its properties, often requiring dilution or downgrading. Scavenging impurities with reactive alloying additions can limit impurity impact and broaden the use of secondary Al. This report will detail the initial results of using Ce to microstructurally tie up Cu impurities present in a model secondary Al alloy (A356) with high Cu impurity. The results show that targeted Ce additions to A356 can be used to scavenge Cu impurities by forming complex intermetallics and inhibit intergranular corrosion susceptibility associated with Cu impurities. Supplemental data for this article is available online at